2011
DOI: 10.2165/11586470-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Prophylactic Lamivudine Use in Preventing Vertical Transmission of Hepatitis B Virus Infection

Abstract: This analysis suggests that supplemental use of lamivudine in mothers with high hepatitis B viraemia is effective in reducing vertical transmission and may be cost effective, from a Taiwanese societal perspective, compared with the routine active-passive immunization without lamivudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…7 Because prevalence data for women with HBV load higher or lower than 10 6 copies/mL are limited, we used 10 6 copies/mL or greater as the lower limit of value defined as high viral load for sensitivity analyses. 7,18,25,27,28 Approximately 10–30% of persons with chronic HBV have viral load 10 8 copies/mL or greater. 7,2527 Consequently, we chose 20% prevalence as our base estimate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Because prevalence data for women with HBV load higher or lower than 10 6 copies/mL are limited, we used 10 6 copies/mL or greater as the lower limit of value defined as high viral load for sensitivity analyses. 7,18,25,27,28 Approximately 10–30% of persons with chronic HBV have viral load 10 8 copies/mL or greater. 7,2527 Consequently, we chose 20% prevalence as our base estimate.…”
Section: Methodsmentioning
confidence: 99%
“…7,18,25,27,28 Approximately 10–30% of persons with chronic HBV have viral load 10 8 copies/mL or greater. 7,2527 Consequently, we chose 20% prevalence as our base estimate. The estimated perinatal transmission rates for pregnant women with HBV load 10 8 copies/mL or greater ranges from 7 to 32%; we used 15% as the base estimate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the estimated results of the five-state model for the Studies 1 and 2 together with other parameters and cost from a previous study (Hung and Chen 2011) as detailed in Appendix 2, Table 6 shows the results of cost, QALYs and the incremental cost-effectiveness ratio. As far as the ICER indicators are concerned, two preventive strategies dominated over no intervention group regardless of study selected because the ICER values were negative, indicating more gain in QALY but less cost (cost-saving) for the two intervention groups as compared with no intervention.…”
Section: Results Of Economic Appraisal On Preventive Strategiesmentioning
confidence: 99%
“…A number of studies have found that the use of lamivudine and telbivudine for MTCT prophylaxis in pregnant HBVinfected women with high levels of viremia is cost effective both in high-income countries such as the USA and Taiwan and in China, a middle-income country [70][71][72]. Without pre-existing advanced liver fibrosis/cirrhosis or hepatitis flare, cessation of antiviral therapy is recommended at delivery, 4-12 weeks after delivery, or when breastfeeding is begun [14].…”
Section: Other Aspects Of Antiviral Treatment During Pregnancymentioning
confidence: 99%